Analisis Saluran Pemasaran Ubi Jalar (Ipomoea batatas .L) Desa Krandegan Kecamatan Bulukerto Kabupaten Wonogiri - Suparno Suparno; Umi Nur Solikah; Irma Wardani; Tria Rosana Dewi (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
Food crops consist of several commodities including rice, corn, sweet potatoes, cassava, peanuts and soybeans. As one of the food ingredients cultivated by farmers, sweet potatoes are a potential food crop in the food diversification program. This study aims to analyze the efficiency of sweet potato marketing channels and marketing margins in Krandegan Village, Bulukerto District, Wonogiri Regency. The location selection was carried out using the purposive sampling technique and sample selection using the snowball sampling technique. The results of the study showed that there are three types of sweet potato marketing channels. The results of the marketing margin analysis showed that wholesalers had the smallest margin value of Rp. 500.00 / kg. Based on the farmer's share analysis, the channel pattern with the largest farmer's share is channel I, which is 100%. The most efficient sweet potato marketing efficiency is channel I, which is 0. Sweet potato marketing does not involve marketing institutions so that there are no sweet potato marketing costs